Refractory ascites: unveiling POEMS syndrome as the underlying cause: a case report and literature review - Liu, Shuang; He, Yin; Qin, Jiamin; Wang, Li; He, Xinhui; Zhou, Yingyue; He, Qin; Kun, Kaixiao; Wen, Liming (Frontiers in Medicine, 2025)
Ascites is a common clinical manifestation usually caused by portal hypertension, hypoalbuminemia, or malignant tumors; POEMS syndrome, a rare cause of ascites, can also lead to refractory ascites. However, due to its low incidence and complex clinical manifestations, this syndrome is prone to being missed or misdiagnosed, resulting in delayed treatment. This article reports an elderly male patient with refractory peritoneal effusion who had multiple unsuccessful treatments. After admission to our hospital’s Department of Gastroenterology, his symptoms persisted despite diuresis and paracentesis. Further inquiry showed he had experienced 2 years of recurrent pruritus, lower limb edema, and occasional numbness. Tests revealed IgA-λ type M proteinemia and elevated VEGF, while imaging showed osteosclerotic lesions and splenomegaly. Finally, He was diagnosed with POEMS syndrome via bone marrow biopsy. After treatment with bortezomib, dexamethasone, and lenalidomide, his symptoms improved significantly. POEMS syndrome, a rare cause of ascites, is frequently missed or misdiagnosed; thus, clinicians should maintain high vigilance. In patients with unexplained refractory ascites and symptoms like neuropathy, organ enlargement, and endocrine disorders, screening for VEGF levels and M protein should be performed to facilitate early identification of POEMS syndrome.